2022
DOI: 10.1177/20552076221139694
|View full text |Cite
|
Sign up to set email alerts
|

ActiveHip+: A feasible mHealth system for the recovery of older adults after hip surgery during the COVID-19 pandemic

Abstract: Objective Half of older adults undergoing hip surgery do not recover their previous functional status. mHealth is a promising tool for rehabilitating older adults after hip surgery. This study aimed to test the feasibility of the ActiveHip+ mHealth system in older adults after hip surgery. Methods Sixty-nine older adults who had undergone hip surgery and their family caregivers were recruited from hospitals in Spain and Belgium and used the ActiveHip+ mHealth system for 12 weeks. Assessments were made during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“… 50 Other chronic diseases or symptoms included pain, 51 type 2 diabetes, 42 , 52 Parkinsonism, 53 rheumatoid arthritis, 54 and obesity. 42 , 55 It is worth mentioning that two studies targeted both older adults and caregivers, 49 , 56 and one study also included grandparents and grandchildren. 57 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 50 Other chronic diseases or symptoms included pain, 51 type 2 diabetes, 42 , 52 Parkinsonism, 53 rheumatoid arthritis, 54 and obesity. 42 , 55 It is worth mentioning that two studies targeted both older adults and caregivers, 49 , 56 and one study also included grandparents and grandchildren. 57 …”
Section: Resultsmentioning
confidence: 99%
“…DHTs encompassed various distinct applications, such as health care services delivered via television, 47 telephone, 51 , 58 , 59 video meeting, 46 , 48 , 49 , 60 social media, 45 , 61 mobile applications, 53 , 56 and website-based telehealth. 50 , 52 , 55 In addition to “traditional” DHTs, several new approaches were implemented in health care sectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that although the Telerehabilitation group had better outcomes in terms of fall efficacy and instrumental ADL performance, the lack of social support in the control group may contribute to this difference [18]. One of the biggest studies about telerehabilitation on hip fracture was by Prieto-Moreno et al [19]. This study included patients from Spain and Belgium, using the Active hip+ mHealth for 12 weeks, and showed high rates of adaptation and usage of active hip+ after hip fracture [19].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 99%
“…One of the biggest studies about telerehabilitation on hip fracture was by Prieto-Moreno et al [19]. This study included patients from Spain and Belgium, using the Active hip+ mHealth for 12 weeks, and showed high rates of adaptation and usage of active hip+ after hip fracture [19]. The study compared the functional recovery of older adults with hip fractures between a multidisciplinary telerehabilitation program and home-based in-person rehabilitation by Ortiz-Piña et al [20].…”
Section: Efficacy Of Telerehabilitation After Hip Fracturementioning
confidence: 99%